Convergence Theorems for Partial Sums of Arbitrary Stochastic Sequences. (24th October 2010) - Wang, Xiaosheng; Guo, Haiying
Abstract : By using Doob's martingale convergence theorem, this paper presents a class of strong limit theorems for arbitrary stochastic sequence. Chow's two strong limit theorems for martingale-difference sequence and Loève's and Petrov's strong limit theorems for independent random variables are the particular cases of the main results.